Nursing of a patient undergoing confocal laser endomicroscopy (1例共聚焦激光显微内镜检查术患者的护理配合体会) - ZHANG Rongwang (张荣旺); WANG Shuang (王爽); PENG Dan (彭丹) (中西医结合护理)
To retrospectively analyze the clinical data of a patient with confocal laser endomicroscopy, and summarize nursing measures such as preoperative preparation, intraoperative coordination, postoperative care of adverse reaction care, psychological care and other targeted nursing interventions. It is required to carried comprehensive nursing interventions to reduce patient discomfort and ensure the success of confocal laser endomicroscopy. (本文总结1例行共聚焦激光显微内镜检查术患者的护理配合要点, 包括术前准备、术中配合以及术后常规护理、不良反应护理、心理护理等针对性护理措施, 以减轻患者不适症状, 保障患者共聚焦激光显微内镜检查的顺利完成。)